2010
DOI: 10.1007/s10815-010-9401-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation, apoptotic gene expression and incidence of numerical chromosomal abnormalities following cryotop vitrification of sheep cumulus-oocyte complexes

Abstract: Purpose The purpose of this study was to evaluate the effects of cryotop vitrification of sheep cumulus-oocyte complexes (COCs) on oocyte maturation, apoptotic gene expression and incidence of chromosomal abnormalities. Methods Freshly isolated (control group) and vitrifiedwarmed COCs (cryotop group) were matured in vitro. The expression of pro-and anti-apoptotic genes was investigated by real-time PCR. The incidence of numerical chromosomal abnormalities was evaluated by cytogenetic analysis. Results The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 48 publications
3
28
0
1
Order By: Relevance
“…These results demonstrated that the use of this technique was not sufficient to activate the apoptotic process. However, induced numerical chromosomal abnormalities that reduced IVM rates was observed (Ebrahimi et al, 2010b). Succu et al (2007a) also reported chromosomal damages in 93% of oocytes vitrified with OPS, 83% with cryotop, and 63% with cryoloop when vitrified in the same concentration of cryoprotectants.…”
Section: Cryoprotectantsmentioning
confidence: 98%
See 2 more Smart Citations
“…These results demonstrated that the use of this technique was not sufficient to activate the apoptotic process. However, induced numerical chromosomal abnormalities that reduced IVM rates was observed (Ebrahimi et al, 2010b). Succu et al (2007a) also reported chromosomal damages in 93% of oocytes vitrified with OPS, 83% with cryotop, and 63% with cryoloop when vitrified in the same concentration of cryoprotectants.…”
Section: Cryoprotectantsmentioning
confidence: 98%
“…Indeed some studies have demonstrated that the vitrification process in sheep oocytes caused damages on morphology, ultrastructure, meiotic spindle and chromosomal arrangement (Succu et al, 2007a;Ebrahimi et al, 2010b;Ebrahimi et al, 2012). These changes can be classified as either reversible or irreversible.…”
Section: Main Damages To Vitrified Oocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the DMSO mechanism of action may impair the ability of cumulus cells to expand during the cytoplasmic maturation process, probably without affecting the nuclear maturity of the oocytes (Cetin & Bastan, 2006;Ebrahimi et al, 2010;Hajarian et al, 2011). Accordingly, as our results showed, the nuclear maturity of the oocytes was not affected resulting in a comparable cleavage rate between DMSO-and PROH-treated groups even if the maturation rate was statistically different.…”
Section: Discussionmentioning
confidence: 45%
“…The activation of the Bcl-2, specifically the pro-apoptotic member genes is performed by the release of cytochrome C which interact with the apoptosis enzyme Apaf-1 and therefore activate caspase 9. The other activation of the anti-apoptotic member of the Bcl-2 gene is through the blocking apoptosis induced by the external stimulus (Ebrahimi et al, 2010) and when the the pro-apoptotic protein BAX is expressed it counteracts the apoptosis-preventing effect of BCL-2 (Somal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%